Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Gender in Political Economy Analysis - Browne, Evie (GSDRC, University of Birmingham, 2014)
This report provides a brief examination of how and where gender analysis is incorporated into Political Economy Analysis (PEA). An initial review of the literature indicates that gender is not systematically included in PEA. This was also conveyed by a number of experts consulted for this report, who stated that few if any PEAs to their knowledge had included a gender analysis, with the issue usually treated only in passing. The report nevertheless highlights the existing examples of gender-oriented analytical questions used in common PEA tools. It also identifies areas of overlap between gender and political economy analysis.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); gender / género

The Environment for Women's Entrepreneurship in the Middle East and North Africa - Chamlou, Nadereh (Orientations in Development, 2008)
This report is about how women entrepreneurs can contribute more to the quality and direction of economic and social development in the Middle East and North Africa (MENA) region. Economic growth in the Middle East has been remarkable since 2004, mainly because of higher oil prices. Rapid job growth has followed, driven mainly by the private sector. Yet the region still faces two important challenges: the first is to create better jobs for an increasingly educated young workforce; the second is to diversify its economies away from the traditional sectors of agriculture, natural resources, construction, and public works and into sectors that can provide more and better jobs for young people— sectors that are more export oriented, labor intensive, and knowledge driven. These goals can be achieved only by more innovative and diverse investors. In this, the private sector must play an even bigger role than in the past. This report is different. Its objective is to provide a better understanding of barriers to investment and doing business that may be common to all investors and those that affect women entrepreneurs disproportionately. The report examines newly available data from more than 4,800 surveyed firms in the formal sector in eight Middle East and North African countries (the Arab Republic of Egypt, Jordan, Lebanon, Morocco, Saudi Arabia, the Syrian Arab Republic, Gaza and the West Bank, and the Republic of Yemen). These surveys detail firm characteristics and the responses of male- and female- owned firms to questions about perceived barriers along 18 categories of the investment climate. The purpose of the report is threefold: • to provide an overview of the characteristics of female- owned firms in the region; • to analyze gender- specific barriers that exist across the region or within countries; and • to identify other factors outside the business environment that might affect women’s entrepreneurship. The report finishes with policy recommendations on how to reduce the identified barriers and create a level playing field for women entrepreneurs. The report acknowledges limitations resulting from the availability and depth of data. It does not attempt to answer every question about women’s entrepreneurship in MENA. Indeed, it may raise more questions than it answers. The hope is to spur greater interest in the topic among researchers and policy makers.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Gender, Entrepreneurship, and Competitiveness in Africa - Bardasi, Elena; Blackden, Mark C.; Guzman, Juan (World Bank, 2007)
This chapter aims to shed light on the nature of men’s and women’s enterprises in Africa, to assess the extent to which the constraints and obstacles faced by women and men entrepreneurs may differ, and to address whether the constraints and obstacles entrepreneurs face affect the productivity and performance of men’s and women’s businesses differently.We begin with a brief overview of gender in the economy, followed by a more detailed analysis of available Enterprise Survey data where key characteristics of businesses can be disaggregated by the sex of the business owner.1 This allows us to look at various characteristics of men’s and women’s businesses, including perceptions of obstacles and constraints, and to assess productivity differences.After briefly placing this analysis in a wider context, the chapter concludes with some recommended actions to address the gender dimensions of entrepreneurship more systematically in policy and programs aimed at supporting private-sector development, along with suggestions for further data collection and analysis.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Gender and economic growthin Kenya: unleashing the power of women - Ellis, Amanda; Cultura, Jozefina; Dione, Nouma; Gillson, Ian; Manuel, Clare; Thongori, Judy (The World Bank, 2007)
This report examines the legal, administrative, and regulatory barriers that are preventing women in Kenya from contributing fully to the Kenyan economy. Building on the 2004 Foreign Investment and Advisory Service (FIAS) report, “Improving the Commercial Legal Framework and Removing Administrative and Regulatory Barriers to Investment,” this study looks at the bureaucratic barriers facing women in Kenya through a gender lens. The report makes specific recommendations to address gender-related barriers in the context of ongoing government and donor initiatives to encourage private sector development as the key driver of poverty reduction and economic growth, in line with Kenya’s Economic Recovery Strategy for Wealth and Employment Creation 2003–2007 (ERS). Addressing these constraints will not only allow women to make a full contribution to the economy but also improve their livelihoods and those of their families and help create a more enabling environment for all businesses in Kenya.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; gender / género; justice / justiça

A gender analysis of the impact of indirect taxes on small and medium enterprises in Vietnam - Akram-Lodhi, A Haroon; van Staveren, Irene (Institute of Social Studies, 2003)
This paper brings together gender analysis, small scale enterprise analysis, and gender budget analysis in a development context. The paper demonstrates that gender matters not only to the ownership of an SME, but also to its most likely principal activity, the stock of the assets that it possesses, the labour that it utilizes, the costs that it faces, the revenues that it generates, and the profits that it earns. In particular, lower earnings for female-owned SMEs can be attributed to the different input cost structures facing female and male-owned SMEs, which in turn are influenced by the indirect tax system. In this context, the paper identifies five gender biases in Vietnam’s VAT system. These biases help explain the higher costs and lower profits of female-owned SMEs in Vietnam. This explanation is different from the more common explanation given for lower performance of female owned enterprises in developing countries, which is the gender segregation of sectors. Although this also plays a role, we argue that gender biases in costs and earnings, partly caused by the tax system, are the more dominant factor.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; gender / género